Microbiological preparations affecting the soil nutrient availability and growth of ryegrass in a pot experiment - Jakab, Anita (Acta Agraria Debreceniensis, 2014)
The effects of different bacterial fertilizers and their combinations with NPK fertilizer and wheat straw were investigated on some soil properties (chemical parameters) and on the biomass production of testplant. The applied quantities of the bacterial fertilizers were the double of the recommended dose. The experiment was set up in 2013 at the Institute of Agricultural Chemistry and Soil Science, in a three replications, in a random block design. Calcareous chernozem soil; originating from Debrecen (Látókép) was used with ryegrass (Lolium perenne L.) test plant. At the end of the experiment (after 8 week) the samples of soil and plants were determined for nitrate-nitrogen, ALsoluble phosphorus and potassium content of soil, the weight of green biomass of ryegrass per pot, the dry matter and moisture content of ryegrass. Straw treatment resulted better water and available nutrient content of soil in general. Inoculation however was not improving the biomass production over the fertilizer treatment. Interrelation with the recommended dose could be further studied.